Characteristics Plastic Blocks from Plastic Waste for Building Wall Materials (PBWBM): Foam Nets and Used Oil - Putu Cinthya Pratiwi Kardita; I Nyoman Arya Thanaya; Muhammad Maheswara Aryasatya; I Komang Edi Perdana Putra (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2025)
According to the Ministry of Environment and Forestry, total national waste in 2021 will reach 68,5 million tons. Of that amount, 17%, or around 11,6 million tonnes, was contributed by plastic waste. Fruit wrapping (foam nets) and thin plastic packaging are examples of plastic waste often found in society. This research will make fruit wrapping nets and use thin plastic packaging into plastic blocks for wall-building material (PBWBM). This research aims to determine the melting temperature, mixture proportions, and solidification temperature and analyze the characteristics of the plastic blocks using fruit wrapping nets, thin plastic packaging, waste motor oil, and rice husk ash filling materials. The PBWBM consisted of three types of samples, namely Mixture A (fruit wrapping net + waste motor oil), Mixture B (fruit wrapping net + used thin plastic packaging + waste motor oil), and Mixture C (fruit wrapping net + waste motor oil + rice husk ash). The right temperature for melting fruit wrapping nets and using thin plastic packaging with waste motor oil is 200 oC. The recommended PBWBM mixture proportion based on trial and error is 800 grams of fruit wrapping net and 600 grams of waste motor oil (compressive strength test results). The ideal compaction temperature ranges from 110 oC-125 oC, IRS test results range from 0,0135-0,0252 kg/m2.minute, water absorption content values range from 0,0281-0,0688%, and porosity values range from 0,720-2,006%. The compressive strength value without immersion was obtained in the range 29,826-42,063 kg/cm2, and the compressive strength value with immersion was obtained in the range 25,728-40,023 kg/cm2. The compressive strength values for the three types of PBWBM have reached the minimum average compressive strength based on BSN 1989 (â‰¥ 25 kg/cm2).